Quantitative Risk Analysis of Asset Information Technology at STT Pagaralam - Buhori Muslim (Institut Teknologi Dirgantara Adisutjipto, 2018)
Information technology (IT) applications in organizations are very important to do this to support the effectiveness and efficiency of the organization's business processes. IT assets are the most important component in the company's business processes (organization) today, which has a high vulnerability to the risks that occur. non-functioning of IT assets because threats (risks) can systematically disrupt performance. The technical implementation unit (UPT) at STT Pagar Alam is responsible for managing IT assets. IT assets that are the object of this research include hardware consisting of monitors, CPUs, projectors, stavolt, printers and laptops with a considerable quantity. departing from the management's needs when identifying risk factors that need to be given maintenance priority and the type of IT assets to identify and measure IT assets using the Quantitative risk analysis (QRA) method so that known aspects and factors need special attention effectively and efficiently. This study produced recommendations on the type of IT assets in the form of CPUs and the types of power loss risk factors that require priority for further control measures.